2012
DOI: 10.1111/j.1468-3083.2012.04619.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy using topical 5‐aminolaevulinic acid vs. surgery for basal cell carcinoma

Abstract: ALA-PDT offers a similarly high efficacy, and a better cosmetic outcome than simple excision surgery in the treatment of BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 19 publications
0
41
0
4
Order By: Relevance
“…Performance of two ALA-PDT treatments for both nodular and superficial BCC has given comparable clinical response rates to surgery (95.83% complete response versus 95.65%). Recurrence rates were also similar (4.16% versus 4.34%) [81]. In the longest follow-up study to date lasting 10 years, Christensen et al [89] found that the overall complete response rate for all subtypes of BCC treated with ALA-PDT was 75%, with a 60% complete response after one treatment and 87% response after two treatments.…”
Section: Basal Cell Carcinomamentioning
confidence: 78%
See 2 more Smart Citations
“…Performance of two ALA-PDT treatments for both nodular and superficial BCC has given comparable clinical response rates to surgery (95.83% complete response versus 95.65%). Recurrence rates were also similar (4.16% versus 4.34%) [81]. In the longest follow-up study to date lasting 10 years, Christensen et al [89] found that the overall complete response rate for all subtypes of BCC treated with ALA-PDT was 75%, with a 60% complete response after one treatment and 87% response after two treatments.…”
Section: Basal Cell Carcinomamentioning
confidence: 78%
“…Rhodes et al [82] showed that the recurrence rate for primary nodular BCC after treatment with PDT was 14% versus 4% with surgical excision at the 5-year follow-up point. Data from other studies support that PDT leads to better cosmetic results compared to surgical excision [81,82]. Also PDT serves as an effective alternative treatment option in difficult cases where an extensive surgical excision should have been performed carrying the risk of a worse cosmetic outcome [84].…”
Section: Basal Cell Carcinomamentioning
confidence: 96%
See 1 more Smart Citation
“…The inflammatory process occurring after seven days following the first PDT session is observed in Figure 1, panel B, which is characterized by enhanced expression of pro-inflammatory cytokines and leukocyte infiltration [16]. Many studies on the efficacy of PDT on BCC have been published [4,17,18]. However, only few studies have reported on the topical application of PDT for the treatment of BCC of eyelid cancer [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with nodular BCC had better response rates with surgery (16/17, 94.12%; P=0.88) than those treated with ALA-PDT (15/17, 88.24%). 72 Blue light PDT alone for BCC is controversial because lesions with a vertical growth greater than 2 mm have not been studied extensively. Clinicians should use ALA-PDT with caution for treatment of BCC, especially nodular BCC, because ALA-PDT did not seem to be an effective option for treatment of nodular BCC in one randomized controlled trial (n=173) with 3-year follow-up; recurrence rates for surgical excision (2.3%) were substantially less compared with PDT (30.3%).…”
Section: Basal Cell Carcinomamentioning
confidence: 99%